A Teacher’s Checklist for Evaluating Treatment Intrusiveness - Carter, Stacy L.; Mayton, Michael R.; Wheeler, John J. (Alberta Journal of Educational Research, 2011)
Teachers are frequently involved in developing and evaluating treatments for problematic behaviors. Along with other members of the interdisciplinary team, they must determine the level of intrusiveness that a treatment may have on a student. Several factors that influence the intrusiveness of treatment procedures are described. These factors were used to develop a checklist that could be used systematically by teachers to evaluate the intrusiveness of treatments recommended by treatment teams. After the checklist was administered to a group of preservice teachers, it was found to be capable of discriminating among several treatment options described in a series of case vignettes. The implications of incorporating such a checklist into the design and implementation of treatments for problem behavior are discussed. Les enseignants sont souvent impliqués dans le développement et l’évaluation de traitements des problèmes de comportement. De concert avec d’autres membres d’une équipe interdisciplinaire, ils doivent déterminer dans quelle mesure un traitement est intrusif pour l’élève. L’article décrit plusieurs facteurs qui influencent le degré de discrétion des procédures. À partir de ces facteurs, on a dressé une liste de vérification dont pourraient se servir les enseignants de façon systématique pour évaluer à quel point les procédures recommandées par les équipes de traitement sont intrusives. La liste a été présentée à un groupe de stagiaires et s’est avérée capable de distinguer plusieurs options de traitement décrites dans une série de vignettes d’étude de cas. S’ensuit une discussion portant sur les conséquences d’incorporer une telle liste de vérification dans la conception et la mise en œuvre de traitements pour les problèmes de comportement.